Providers perspectives on self-regulation impact their use of responsive feeding practices in child care. (1st November 2017) - Dev, Dipti A.; Speirs, Katherine E.; Williams, Natalie A.; Ramsay, Samantha; McBride, Brent A.; Hatton-Bowers, Holly
Abstract: Supporting children's self-regulation in eating through caregivers' practice of responsive feeding is paramount to obesity prevention, and while much attention has been given to supporting children's self-regulation in eating through parents' responsive feeding practices in the home setting, little attention has been given to this issue in childcare settings. This qualitative study examines childcare providers' perspectives on using responsive feeding practices with young children (2–5years). Individual semi-structured interviews were conducted with providers until saturation was reached. Data was analyzed using thematic analysis. The final sample included 18 providers who were employed full-time in Head Start or state-licensed center-based childcare programs, cared for children (2-5y), and were directly responsible for serving meals and snacks. Providers were primarily (67%) employed in childcare programs that served children from low-income families and received reimbursement for meals and snacks from the US Department of Agriculture's Child and Adult Care Food Program. Three factors emerged that shaped childcare providers' experiences using responsive feeding practices: the providers' perspectives about whether or not young children can self-regulate food intake, their understanding of Child and Adult Care Food Program (CACFP) portion size regulations, and the availability of food at the center where they worked. Future research should examine how childcare providers' understanding of children's ability to self-regulate their food intake, the appropriate use of the CACFP regulations in relationship to serving sizes, and having food available to offer seconds promotes providers' use of responsive feeding practices in center-based childcare programs and children's dietary behaviors.